Man-eating monsters : anthropocentrism and popular culture - Khapaeva, Dina (Emerald studies in death and culture., 2019)
What role do man-eating monsters - vampires, zombies, werewolves and cannibals - play in contemporary culture? This book explores the question of whether recent representations of humans as food in popular culture characterizes a unique moment in Western cultural history and suggests a new set of attitudes toward people, monsters, animals, and death.This volume analyzes how previous epochs represented man-eating monsters and cannibalism. Cultural taboos across the world are explored and brought into perspective whilst we contemplate how the representations of humans as commodities can create a global atmosphere that creeps towards cannibalism as a norm.This book also explores the links between the role played by the animal rights movement in problematizing the difference between humans and nonhuman animals. Instead of looking at the relations between food, body, and culture, or the ways in which media images of food reach out to various constituencies and audiences, as some existing studies do, this collection is focused on the crucial question, of how and why popular culture representations diffuse the borders between monsters, people, and animals, and how this affects our ideas about what may and may not be eaten.